Non-Syndromic Orofacial Cleft Malformations in Jeddah, Saudi Arabia - Sabah S. Moshref; Yasir S. Jamal; Mahmoud Fakiha; Basim A. Awan; Fayza Alsiny; Fatma Alzhrani; Hossam Ammar; Abdullah Bamashmos; Abeer Baamer (Journal of King Abdulaziz University: Medical Sciences, 2023)
This retrospective, hospital based study aims to investigate demographic and clinical characteristics of pediatric patients with orofacial cleft in Jeddah, Saudi Arabia from 2005 to 2015. Hospital surgical records from three main sources, King Abdulaziz University Hospital, Bagedo and Dr. Erfan Hospital and Dr. Soliman Fakeeh Hospital were used to identify all consecutive surgical cases with orofacial cleft referred to these hospitals. Information about age, sex, cleft types, site, maternal risk factors, associated pediatrics problems and treatment were recorded. The most common type was cleft lip and palate (40.15%), then isolated cleft palate (35.61%) and isolated cleft lip (24.24%). Maternal risk factor was mostly smoking (4.55%); pediatrics complication was mostly speech abnormalities and dental problems (75.00%); post-operative complication was mostly speech abnormalities (72.54%). Our study reveals that epidemiologic aspects of orofacial cleft in Jeddah are very similar to other Caucasian populations with a predominance of cleft lip, unilateral left side. Routine screening such as chest x-ray and ruling out hearing and speech problems as well as genetic counseling and karyotyping may be necessary in these patients. Better understanding of demographic and clinical characteristics may help guide clinical care as well as contribute to an improved understanding of pathogenesis.